Aplikasi Survei Ubinan Berbasis Android - Betti Noviyani; Eko Budi Setiawan (Ultimatics : Jurnal Teknik Informatika, 2018)
Central Bureau of Statistics is one of the institutions that collect data in all fields and one of them is data of food crops. The Central Bureau of Statistics conducted the ubinan survey to obtain food crop data. Found some obstacles in the field in conducting ubinan survey. This can reduce the quality of food crop data if not quickly addressed. Given food crop data is very important for the life of the community, it takes a tool that can help the surveyor so that the data produced can be more quickly and accurately. In this research will be made an application with a given feature that is to store the coordinate point of survey implementation, to provide location information on harvest measurement in the field, to detect harvest income writing errors, display compass as a tool for determining the direction of the wind. So that the work of ubinan survey can be further improved the quality of food crop data in the Central Bureau of Statistics. Index Terms— Android, Survei, Ubinan, Tanaman Pangan.